Family Psychoeducation in Improving Problem Solving Skills in Family with Drugs Abusers Family Members - Robby Prihadi Aulia Erlando; Novy Helena Catharina Daulima (Jurnal Ilmu Keperawatan Jiwa, 2020)
The family is a system that interacts between members to achieve common goals. This interaction is needed to help family members who have health problems such as drug abuse. This recovery process is felt not only by clients who experience illness, but also caregivers who play a role in helping recovery so that not a few caregivers felt stress with conditions like this. Providing information related to the client's illness and how to take care of health has been provided after the client returns from treatment at the rehabilitation agency. The next treatment is done at home, this will affect the lifestyle of family members who are at home and can cause psychosocial problems for caregivers. Family psychoeducation is expected to be able to overcome problems with the client as well as the caregiver during the recovery process is done and improve the ability of families to solve problems. The method in this writing is the study of literature by selecting from several electronic journals The results showed that psychoeducation can increase the ability of caregivers and reduce the burden experienced by caregivers.